Tacrolimus-induced optic neuropathy ¬– a case report - Žorić, Lepša; Ilić, Aleksandra; Čolak, Emina; Mirković, Miloš; Pantelić, Jelica; Mirić, Dijana; Kisić, Bojana (Vojnosanitetski pregled, 2022)
Introduction. Tacrolimus (fujimycin or FK506) is a potent immunosuppressive drug with growing usage. It is usually used in the prevention of transplanted organ rejection. Its use is highly valuable, but like other immunosuppressants, it has adverse effects. One of them is optic neuropathy. Case report. A 47-year-old male patient, who had received tacrolimus therapy for nine years after kidney transplantation, developed a subacute, painless vision loss in both eyes. He was thoroughly examined on different possible optic neuropathies and other causes of vision loss. After exclusion of other possible causes, the diagnosis of toxic optic neuropathy was established. The patient’s therapy was converted to cyclosporine by his nephrologist, but his vision had improved only slightly. Conclusion. Toxic optic neuropathies are presented in everyday ophthalmological practice, but they are underestimated. Diagnosis can be demanding, especially when it comes to drugs and substances whose possible toxic effect on the optic nerve is not widely known. Unlike other adverse effects of tacrolimus therapy on the nervous system, optic neuropathy can cause great and permanent functional impairment.